Movement development stages in learning discus throwing for beginners - حسن جلاب, سليم; محمد سعيد, سندس (Journal of Physical Education, 2019)
In an attempt to progress the discuses throwing process, is vital to develop performance outcome level within beginners. The research aims to introduce the problems faced within each of learning process stages for discus throwing . The research hypotheses the existence of motion stages within its harmony and motion flow to execute good motion performance. The research sample consisted motor learning sport training and track games specialists and had employed Arabic and foreign references . it was concluded that each of the learning stages has its own learning specialty in discus throwing throughout each technical stage of motion . The research recommend the importance of employing the learning method within the research has its prime affect on the sports man